Functional Outcome After Neglected Injury In Pediatric Softball Players Measured By Quickdash Score - Yoyos Ismiarto; Sabdillah FT; Ramli F; Kemas Abdul Mutholib Luthfi (HM Publisher, 2020)
A B S T R A C T Introduction : Pediatric softball players are prone to get injured as a result of high forces motions, with improper technique. Low communication and school-age often leads the injury became neglected. The aim of this study is to determine the incidence of Neglected injury in pediatric softball players in Bandung during a single season year of 2019. Method : The study was conducted in softball clubs in Bandung. The inclusion is the softball players aged 18 years old or below, grouped into; (1)never injured, (2)neglected injury by non-professional/traditional massage, and (3)untreated neglected injury/rest only. The samples were evaluated with the Quick Disabilities of the Arm Shoulder and Hand outcome questionnaire (QuickDASH). Data was analyzed with Anova test. Result : Among the 50 players, aged from 12 to 18 years old, 36 players (72%) were at group 1, 8 players (16%) were at group 2 and 6 players (12%) were at group 3. Most site of injuries for group 2 are at shoulder (62,5%) and group 3 are at elbow (66,6%). Significant differrences were identified between three groups with p=0.001. The highest quickDASH score are in group 2 (38,6), and the lowest are in group 1 (0,0). Conclussion : All of the quickDASH Score in this group of age are categorized in mild difficulty. Those whom treated by non-professional has lower functional outcome compared to never injured and untreated injured players.